ASSESSMENT OF RESISTANCE IN TOMATO GENOTYPES AGAINST BACTERIAL WILT DISEASE (RALSTONIA SOLANACEARUM) IN ASSAM CONDITION - B. C. NATH; L. C. BORA; Kh. MALEMNGANBA; G. C. BORA (The Bioscan, 2015)
An investigation was carried out at experimental garden for Horticultural crops, Department of Horticulture, Assam Agricultural University, Jorhat with forty-seven genotypes of tomato to assess bacterial wilt (Ralstonia solanacearum) resistance. The experiment was conducted consecutively for two years during Rabi seasons of 2012-13 and 2013-14 following randomized block design with 3 replications. Wilt incidence was calculated till the harvesting stage for each genotype. The check genotypes used in the experiment were Pusa Ruby (susceptible check) and Konbilahi (Lycopersicon pimpinellifolium) [resistant check]. The genotypes were graded as Resistant(R), Moderately Resistant (MR), Moderately Susceptible (MS) and Susceptible(S) following the standard scale. Highly resistance reaction (HR) was recorded in Konbilahi (L. pimpinellifolium) followed by resistance reaction (R) in Sel-35, sel-19 and Sel-9. Highest yield was recorded in 2012/TOLCVRES-3 (278.16 q/ha) followed by H-24 (276.85 q/ha) and 2012/TOLCVRES-4 (272.04 q/ha). The genotypes with resistance reaction could be considered as a promising breeding material for development of high yielding bacterial wilt resistant tomato variety.